Study of Low-Grade Zinc Sulphide Ore Bioleaching Using Acidithiobacillus ferrooxidans - Deng, Xiaorong; Zeng, Guisheng; Li, Hui; Yang, Dajing (Asian Journal of Chemistry, 2012)
In this work, a comprehensive modelling study of the zinc sulphide bioleaching with Acidithiobacillus ferrooxidans was investigated. The effects of particle size, pulp density, stir time, pH and ferrous iron on the bioleaching of zinc were evaluated. Experimental results show that the strains isolated from acid mineral drainage and cultivated in 9/2K medium resulted in high metabolic activities. The bioleaching rates of zinc decreased with the increasing of ore sizes and highest leaching rate of zinc was achieved at the ore size 0.14 mm, pulp density 10 %, stir time 9 days, pH value 1.5-2.0 and 9/2 K medium.